2014
DOI: 10.1055/s-0034-1384536
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Supplementation with Curcuminoids on Systemic Inflammation in Patients with Knee Osteoarthritis: Findings from a Randomized Double-Blind Placebo-Controlled Trial

Abstract: Significant improvement in clinical symptoms of OA in curcuminoid-treated subjects cannot be attributed to the systemic anti-inflammatory effects of these phytochemicals.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
64
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 68 publications
(66 citation statements)
references
References 36 publications
1
64
0
1
Order By: Relevance
“…In this research, no major toxicity was reported but hypertension and tachycardia were reported in one person and also redness of tongue was observed in another person (Nakagawa et al, ). In other clinical research projects, no major toxicity was reported in patients with osteoarthritis who treated with 1,500 mg/day of curcuminoids orally for 6 weeks and patients who received 1.5 g/day curcumin within 6 weeks (Panahi, Rahimnia, et al, ; Rahimnia, Panahi, Alishiri, Sharafi, & Sahebkar, ). There were no severe adverse events in prediabetic individuals who received 1.5 g/day curcumin for 3 months, but itching was reported in one patient and constipation was observed in two patients (Chuengsamarn, Rattanamongkolgul, Luechapudiporn, Phisalaphong, & Jirawatnotai, ).…”
Section: Resultsmentioning
confidence: 96%
“…In this research, no major toxicity was reported but hypertension and tachycardia were reported in one person and also redness of tongue was observed in another person (Nakagawa et al, ). In other clinical research projects, no major toxicity was reported in patients with osteoarthritis who treated with 1,500 mg/day of curcuminoids orally for 6 weeks and patients who received 1.5 g/day curcumin within 6 weeks (Panahi, Rahimnia, et al, ; Rahimnia, Panahi, Alishiri, Sharafi, & Sahebkar, ). There were no severe adverse events in prediabetic individuals who received 1.5 g/day curcumin for 3 months, but itching was reported in one patient and constipation was observed in two patients (Chuengsamarn, Rattanamongkolgul, Luechapudiporn, Phisalaphong, & Jirawatnotai, ).…”
Section: Resultsmentioning
confidence: 96%
“…In another study, administration of two capsules containing curcumin 150 mg twice daily by patients with T2DM for 8 weeks significantly decreased CRP, IL‐6, and TNF‐α levels (Usharani et al, ). Also, following 1,500 mg/day curcuminoid ingestion for 6 weeks Rahimnia, Panahi, Alishiri, Sharafi, and Sahebkar () showed significant reduction in circulating levels of IL‐6 and hs‐CRP, and not serum levels of TNF‐α. However, discrepant results in other studies showed that, for example, consuming curcuminoids (1 g/day) for 30 days by obese patients did not change CRP levels (Mohammadi et al, ).…”
Section: Discussionmentioning
confidence: 97%
“…A key mechanism for the modulatory effects of curcumin on pro inflammatory cytokines is the suppression of NF-κB ( (Banerjee, Tripathi, Srivastava, Puri, & Shukla, 2003;Clutterbuck et al, 2009;Davis et al, 2007;Jagetia & Aggarwal, 2007;Mathy-Hartert et al, 2009;Rahimnia et al, 2015). The effects of curcumin on the production of key cytokines and chemokines is shown in Table 1.…”
Section: The Effects Of Curcumin On Cytokine Production and Inflammmentioning
confidence: 99%